The Effect Of Parental Motivation On Students' Learning Interest In The Accounting Expertise Program At SMKN 1 Makassar - Nur Huzaemah; Sahade Sahade; Fajriani Azis (Lembaga Riset, Publikasi dan Konsultasi JONHARIONO, 2023)
This study aims to determine the effect of providing motivation by parents on the learning interest of class X students of the Accounting Expertise Program at SMK Negeri 1 Makassar. The variables in this study are motivation given by parents as the independent variable and interest in learning as the dependent variable. The population in this study was all class X students of the accounting skills program at SMKN 1 Makassar. The sample technique used a proportionate stratified random sampling technique of 60 students. Data analysis used descriptive tests, hypothesis testing consisting of simple linear regression analysis, Pearson product moment correlation analysis, the coefficient of determination, and the t-test. Based on the results of the data analysis that has been carried out, a simple linear regression equation model is obtained: Y = 30.320 + 0.472X, which means that for each addition of 1 unit of motivation given by parents, the interest in learning has increased by 0.472. From the results of the analysis of the coefficient of determination (r2), the value of r2 = 0.414 is obtained, which means that the effect of motivating parents on learning interest is 41.4% and the remaining 58.6% is influenced by other factors. Meanwhile, based on the results of the Pearson product moment correlation analysis, a correlation coefficient of 0.643 was obtained and it was in the strong category, which means that there is a strong relationship between giving motivation by parents and the learning interest of class X students in the accounting expertise program at SMK Negeri 1 Makassar. While the results of the t-test analysis obtained a significant value of 0.000<0.05, which means that giving motivation by parents has a significant effect on interest in learning, the hypothesis is accepted.